Design Perceptions for 3D Printed Accessories of Digital Devices and Consumer-Based Brand Equity - Meng, Yuke; Bari, Muhammad Waseem (Frontiers in Psychology, 2019)
Drawn on means-end theory and relationalism, this study investigates the impact of 3D printed branded accessories’ design perception on consumer-based brand equity (CBBE). In addition, how experiential value mediates the relationship between product design perception and CBBE. Based on a random sampling approach, the present study collected 535 3D printed branded accessories users’ response through social media (WeChat). The data were analyzed through partial least squares, structural equation modeling (PLS-SEM) approach, smart PLS-3. The results reveal that two dimensions of design perception (functional and kinesthetic) have a significant impact on CBBE. However, design perception (visual) has failed to impact significantly on CBBE. The experiential value significantly mediates the relationship between all dimensions (visual, functional, and kinesthetic) of design perception and CBBE. This study concludes that experiential value/ user experience is an inevitable mediator between product design perception CBBE. The implication and limitations of this study are discussed in the last section of this study.